Sick and tired : an intimate history of fatigue - Abel, Emily K. (Studies in social medicine., 2021)
"Blending vivid auto-ethnography with historical and cultural analysis, this book examines three themes common to the experience of chronic fatigue patients. The first is the denigration of subjective knowledge in the medical community. Since there are no tools with which to diagnose fatigue, there can be no medical confirmation, making it difficult to convince doctors, and often by extension the patients themselves, that these problems are real. Without a diagnosis, there are no prescribed guidelines and as a result, patients often create alternative cultural spaces in the form of support groups that give primacy importance to the role of subjective experience. Chronic fatigue syndrome advocates have repeatedly called attention to the paltry amount of research funds directed to that condition. Because everyone gets tired and endures aches and pain at some point, the public also dismisses persistent pain and fatigue. The second is an analysis of the cultural emphasis on productivity. Although Abel was reluctant for many years to view her fatigue as a disability, its impact on her life immediately forced her to face some of the most emotionally charged and persistent questions about work and morality: In a society that places inordinate emphasis on work ethic, who is entitled to remain idle? How can unemployed people find another source of human worth? When does devotion to work become excessive? Finally, Abel examines the prevalence of personal triumphal narratives in the cultural production of recovery"--